2014
DOI: 10.1002/jcla.21749
|View full text |Cite
|
Sign up to set email alerts
|

Soluble l‐Selectin as an Independent Biomarker of Bronchial Asthma

Abstract: Our study suggests that plasma level of sL-selectin is an independent biomarker for asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 36 publications
(48 reference statements)
5
6
0
Order By: Relevance
“…In this study, the Leu/Leu genotype was shown to be the least frequent genotype in the whole population. This result is similar to previous studies in the same population, which reported the Phe/Phe genotype as the major homozygote genotype …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, the Leu/Leu genotype was shown to be the least frequent genotype in the whole population. This result is similar to previous studies in the same population, which reported the Phe/Phe genotype as the major homozygote genotype …”
Section: Discussionsupporting
confidence: 93%
“…Our results showed significantly higher serum levels of L‐selectin in TB patients versus the healthy controls. In some studies, L‐selectin has been shown to be upregulated on immune cells in many infectious diseases and inflammatory responses; this finding is consistent with our results . Moreover, it has been shown that suppression of L‐selectin increases the risk of infection and can compromise cell‐mediated immune reactions .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…38 CCRs are the one category of protein receptors that could regulate cell activities of various types of leukocytes. 45 55 Some studies have also reported that SELE-mediated adhesion of leukocytes or tumour cells to the vascular endothelium was an important progress in the initiation of inflammatory response and metastasis of cancer cells. We therefore speculated that chemokine CCL5 In OA, we discovered that all genes in DEGsOA (coexpressed genes and OA-specific genes) were all playing the role of promoting inflammation progress by activating TNF signalling pathway.…”
Section: Identify Biomarkers and Pathway In Ramentioning
confidence: 99%